2016
DOI: 10.7326/m15-0424
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Outcomes in Adult Survivors of Childhood Cancer Exposed to Cardiotoxic Therapy

Abstract: Background Studies of cardiac disease among adult survivors of childhood cancer have generally relied upon self-reported or registry-based data. Objective Systematically assess cardiac outcomes among childhood cancer survivors Design Cross-sectional Setting St. Jude Children's Research Hospital Patients 1,853 adult survivors of childhood cancer, ≥18 years old, and ≥10 years from treatment with cardiotoxic therapy for childhood cancer. Measurements History/physical examination, fasting metabolic and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(120 citation statements)
references
References 44 publications
6
110
1
Order By: Relevance
“…The high prevalence of obesity, the metabolic syndrome and other constellations of cardiovascular disease risk factors among ALL survivors is particularly concerning given their increased risk for both GHD and adverse cardiovascular outcomes [4, 53, 54]. Although previous treatment exposures are a fixed risk factor in the long-term follow-up setting, individual components of the metabolic syndrome are potentially modifiable, representing an area where targeted surveillance and secondary prevention strategies are needed.…”
Section: Prevention and Treatment Approachesmentioning
confidence: 99%
“…The high prevalence of obesity, the metabolic syndrome and other constellations of cardiovascular disease risk factors among ALL survivors is particularly concerning given their increased risk for both GHD and adverse cardiovascular outcomes [4, 53, 54]. Although previous treatment exposures are a fixed risk factor in the long-term follow-up setting, individual components of the metabolic syndrome are potentially modifiable, representing an area where targeted surveillance and secondary prevention strategies are needed.…”
Section: Prevention and Treatment Approachesmentioning
confidence: 99%
“…36 The elevated risk of developing cardiovascular disease could be confounded by pre-existing genetic, lifestyle, age, endocrine, and environmental factors unique to each cancer patient (Figure 1). However, these factors, as well as traditional cardiovascular disease risk factors (obesity, dyslipidemia, insulin resistance, and tobacco use), 4,5 do not fully account for the increased incidence of cancer therapy-induced cardiovascular toxicity. 18 The main cancer therapies reported to induce cardiovascular dysfunction and disease are radiation, vascular endothelial growth factor (VEGF) inhibitors, which encompass tyrosine kinase inhibitors (TKIs) sorafenib and sunitinib, as well as monoclonal antibodies bevacizumab and ramucirumab, human epidermal growth factor receptor type 2 (HER2) monoclonal antibody trastuzumab, and chemotherapeutic agents such as anthracyclines, platinum-based antineoplastic drugs, microtubule inhibitors, and antimetabolites.…”
Section: Clinical Definitions and Guidelines For Cardiotoxicity Aftermentioning
confidence: 99%
“…Interestingly, several studies have demonstrated a poor correlation between traditional cardiovascular risk factors such as obesity, dyslipidemia, insulin resistance, and tobacco use, with the onset of cardiovascular disease in cancer survivors, 4,5 suggesting an alternative mechanism for systemic cardiovascular toxicity. One such mechanism could be inappropriate immune system activation, which has an active role in both cancer and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent cross-sectional cohort study of survivor outcomes, 7.4% of males and females had cardiomyopathy and 3.8% had coronary artery disease. 10 These risks are associated with anthracyclin drugs, specifically doxorubicin, and radiation therapy to the pleural region. As gonadal damage can also occur from these treatments, dissecting the contribution of endocrine dysfunction to disease progression is an important challenge for future research relevant to this patient population.…”
mentioning
confidence: 99%